Comparative study of functional training and traditional resistance training on lower-limb strength performance in male adolescent volleyball players: a randomized controlled trial - Gao, Yuan; Yang, Yale; Xian, Chenyang; Wang, Zetao (Frontiers in Physiology, 2025)
BackgroundThis study aimed to compare the effects of a functional strength-training program designed around volleyball-specific movements with those of traditional resistance training on lower-limb performance in male adolescent volleyball players.MethodsIn a randomized controlled trial, 52 male volleyball athletes (age 13 ± 2 years; ≥2 years of formal volleyball training) from a sports school in Huangshi, Hubei Province, China, were allocated 1:1 to a functional training group (n = 26) or a traditional resistance training group (n = 26). The intervention lasted 12 weeks, with three 90-min sessions per week. Pre- and post-training assessments of lower-limb strength and overall fitness included six measures: standing reach height, approach reach height, half-meter square agility test, standing long jump, 30 m sprint, and 1,500 m run. Data were analyzed in SPSS version 26.0 using paired-samples and independent-samples t-tests, with α = 0.05.ResultsIn the functional training group, standing reach height increased from 2.81 ± 0.10 m to 2.88 ± 0.09 m (P = 0.025), and approach reach height from 2.87 ± 0.12 m to 2.95 ± 0.11 m (P = 0.034). The half-meter square agility time decreased from 18.09 ± 0.98 s to 17.50 ± 1.06 s but did not reach statistical significance (P = 0.075). In the traditional resistance training group, only the half-meter square agility test showed a significant improvement (P = 0.028), with no significant changes in the other five measures (all P > 0.05). Between-group comparisons revealed no significant differences across any outcome (all P > 0.05).ConclusionFunctional training appears superior to traditional resistance training for enhancing lower-limb explosive power in adolescent volleyball players, whereas traditional resistance training retains an advantage in agility. We recommend integrating both functional and traditional strength modalities in youth volleyball conditioning to foster comprehensive development of lower-limb strength and sport-specific performance.